Joint estimation of carrier frequency offset and in-phase/quadrature-phase imbalances for orthogonal frequency division multiplexing systems. (November 2015) - Zhuang, Yanyan; Wan, Yi
Abstract: Orthogonal frequency division multiplexing (OFDM) has been adopted in various high-speed wireless communication systems. OFDM systems using direct-conversion transceivers are gaining much interest because of low cost and power. However, such systems can suffer from carrier frequency offset (CFO) and transmitter (TX)/receiver (RX) in-phase/quadrature-phase (I/Q) imbalances. These impairments may have a tremendous impact on the performance and cannot be efficiently eliminated in the analog domain. In this paper, we propose an efficient joint estimator for CFO and TX/RX I/Q imbalances in the digital baseband domain. The proposed method designs a training sequence at the transmitter that isolates the estimation of TX I/Q imbalance from the other parameters. At the receiver, we form a sinusoidal sequence from the received signal, which is used to jointly estimate the CFO and RX I/Q imbalance iteratively through the maximum likelihood estimation (MLE). Then we estimate the TX I/Q imbalance using the ratio of the estimated sequences just before CFO and RX I/Q imbalance with previously estimated parameters. Simulation results confirm the advantages of the proposed method over existing algorithms in terms of efficiency and estimation accuracy.